Prototype expert system to assist with the stabilization of neonates prior to transport. - Heermann, L. K. (American Medical Informatics Association, 1997)
The transport of sick or premature newborns from community hospitals to acute care facilities is often necessary for the infants to receive the level of care required. Prior stabilization of these infants is imperative to a successful transport. The knowledge required to treat and stabilize sick and premature newborns is specialized and may not be available in community hospitals. "The S.T.A.B.L.E. Assistant" is a prototype rule based decision support system based on the educational program "Transporting Newborns the S.T.A.B.L.E. Way". "The S.T.A.B.L.E. Assistant" accepts clinical information related to an infant's breathing status, blood glucose status and selected lab values and provides instructions as to what interventions are needed to stabilize and prepare the infant for transport. The computerized program was evaluated using data collected from 19 charts of newborns requiring transport from a community hospital to a tertiary care center. Patient data were entered into the computerized program and the subsequent instructions were reviewed by a group of neonatology and neonatal transport experts. Reviewers evaluated "The S.T.A.B.L.E. Assistant" for the safety of the program, the extent to which the computerized program follows the educational program guidelines and the degree to which the instructions generated are within the scope of community caregivers' practice. Results were positive, indicating "The S.T.A.B.L.E. Assistant" prototype is safe, and within the guidelines of neonatal clinical practice.